2014
DOI: 10.1007/s13197-014-1283-0
|View full text |Cite
|
Sign up to set email alerts
|

Rheological of chocolate-flavored, reduced-calories coating as a function of conching process

Abstract: Continuous flow and linear viscoelasticity rheology of chocolate coating is studied in this work using fat substitute gums (xanthan, GX). An alternative conching process, using a Rotor-Estator (RE) type impeller, is proposed. The objective is to obtain a chocolate coating material with improved flow properties. Characterization of the final material through particle size distribution (PSD), differential scanning calorimetry (DSC) and proximal analysis is reported. Particle size distribution of the final materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, it was concluded that all samples were in Form V, the most convenient form, without being affected by fat content and PSD. Medina‐Torres, Sanchez‐Olivares, Nuñez‐Ramirez, Moreno, and Calderas (2014) found that T peak values did not change upon PSD in chocolate coatings. Another insignificant change was observed in T index values, representing the curve's width.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was concluded that all samples were in Form V, the most convenient form, without being affected by fat content and PSD. Medina‐Torres, Sanchez‐Olivares, Nuñez‐Ramirez, Moreno, and Calderas (2014) found that T peak values did not change upon PSD in chocolate coatings. Another insignificant change was observed in T index values, representing the curve's width.…”
Section: Resultsmentioning
confidence: 99%